Azerbaijani-Georgian Literary Relations through Historical Development Process - Chobanov, Mushvig (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2017)
During investigating the development trends of the Azerbaijani literature arose in Georgia in 1960-2010th years, we can see that our scientists, lived-created here, have conducted a number of successful researches in the field of literature and literary criticism and got achievements in the development and research of Azerbaijan- Georgian literary relations. If in 50-60th years of XX century Z. Borchali, A. Mursaloglu and others worked hard in this field, but after 1970 this tradition was followed by professors such as H. Valiyev, A. Musayev, M. Hajikhalilov, F. Khubanli, Sh. Shamioglu, T. Isabalagizi and others honorably. They published numerous articles in different press organs, as well as gave these research works to the discretion of wide range of readers in books form. Looking through the Azerbaijani- speaking press organs, literary journals and collections published in Georgia in the second half of the 20th century, as well as the books of separate authors published in Baku and Tbilisi, it is clear that artistic translation takes an important place in the creativity of writers, lived-created in Georgia and they do not work in this field, no less. Whereas they fulfilled such a glorious task adequately as translating of number of the samples from Georgian literature into our native language, delivering of spiritual word wealth of the neighboring nation to Azerbaijani readers and so firming of spiritual friendship bridge arches existed between our nations for centuries. That’s why we call them “Friendly voices – Translation Masters”. The path of late D. Aliyeva, T. Huseynov, M.H. Bakhtiyarli, A. Sarajli, I. Ismayilzadeh, V. Rustamzadeh, A. Abdulla, Z. Yagub with special contributions in the field of literary translation, was maintained by D. Karam, A. Binnetoglu, M. Chobanzadeh, H. Valiyev, E. Elsevar, S. Suleymanli, N. Nasibzadeh, V. Hajiler, Sh. Mammadli, I. Mammadli, N. Abdulrahmanli, E. Allazolgu, M. Mammadoglu, R. Hummat, A. Khansultanli, J. Mammadli, O. Kazimli and others successfully and they acquainted themselves in this direction. Their translations published in different press organs periodically, especially in some newspapers such as East Lights, Georgia, Existence, in some collections (Spring, 1980; Morning Star, 1987, 1989, 1990; Two hearts in a chest 1981; Literary Georgia, 2007, 2012 and so on.) are interesting and mentionable in terms of not only qualities of literary translation, but also artistic- aesthetic capacity and the position in the national literature. In particular, the translation creativity of our compatriots who know fluently the Georgian language, Georgian literature, the history of Georgian people, future and psychological mood, is heavier and more successful.